Marker‐assisted backcrossing to develop foliar disease‐resistant genotypes in TMV 2 variety of peanut (Arachis hypogaea L.). (27th November 2017) - Kolekar, Rohini M.; Sukruth, Mallenahally; Shirasawa, Kenta; Nadaf, Hajisaheb L.; Motagi, Babu N.; Lingaraju, Sattigarahalli; Patil, Prakashgouda V.; Bhat, Ramesh S.
Abstract: TMV 2 is a very popular peanut variety among the Indian farmers, but it is highly susceptible to fungal foliar diseases like late leaf spot (LLS) and rust. Marker‐assisted backcrossing (MABC) in TMV 2 using foliar disease‐resistant donor, GPBD 4 and the disease resistance‐linked markers (GM2009, GM2079, GM2301, GM1839 and IPAHM103) resulted in a large number of backcross populations and also straight cross populations. Foreground selection followed by field evaluation under disease epiphytotic conditions could identify a few superior genotypes. Two homozygous backcross lines TMG‐29 and TMG‐46 showed enhanced resistance to LLS and rust diseases (score of 3.00 for both) along with 71.0% and 62.7% increase in the pod yield per plot, respectively, over the check, TMV 2. These foliar disease‐resistant and productive lines can be released as commercial varieties or can be used as genetic resources in the peanut improvement.